2012
DOI: 10.1097/qai.0b013e3182615b62
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of c-ART in HIV-1 Infected Patients Is Associated With a Decrease of the Metabolic Activity of the Thymus Evaluated Using FDG-PET/Computed Tomography

Abstract: A metabolic thymic activity is detectable in c-ART naive and correlates with indirect phenotypic and molecular markers of thymic output. This activity may participate to the pool of peripheral naive CD4+ T cells and predicts the magnitude of T-cell reconstitution under treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Our results demonstrate the maintenance of effective lymphopoiesis in HIV-2 infection, which is likely to be linked with a capacity to sustain the long-term production of naive CD8 + T cells. In HIV-1 infection, the progressive decrease in naive T cell proportions in HIV-infected adults likely results from the Ag-driven maturation of these cells in the absence of adequate T cell renewal capacity because of the declining thymic output of new cells (8,10,24). We and others previously reported that thymic function is preserved in HIV-2-infected individuals with low viral load (25).…”
Section: Cd45ramentioning
confidence: 99%
“…Our results demonstrate the maintenance of effective lymphopoiesis in HIV-2 infection, which is likely to be linked with a capacity to sustain the long-term production of naive CD8 + T cells. In HIV-1 infection, the progressive decrease in naive T cell proportions in HIV-infected adults likely results from the Ag-driven maturation of these cells in the absence of adequate T cell renewal capacity because of the declining thymic output of new cells (8,10,24). We and others previously reported that thymic function is preserved in HIV-2-infected individuals with low viral load (25).…”
Section: Cd45ramentioning
confidence: 99%
“…As expected, the results of this study showed lower percentage of naive CD8 T cells in HIVinfected MSM compared to uninfected controls. This may be partially explained by the capacity of the thymus to produce new T cells or thymic output, which is signi cantly decreased during the course of HIV infection [31][32][33]. Moreover, our results indicate that naive CD8 T cells in HIV-infected MSM are more activated and show a more replicative senescence phenotype.…”
Section: Discussionmentioning
confidence: 73%
“…Lilievere et al 2012 [18] J Acquire immune Defic Syndr Clinical Evaluated thymic activity with FDG uptake and precursors for thymic activity. Thymic uptake was lower in HAART-treated patients compared with age-matched controls.…”
Section: Liu Et Al 2009mentioning
confidence: 99%
“…In HIV-infected patients treated with HAART metabolic uptake in the thymus has been shown to be a non-invasive marker of thymic output. Patients without thymic uptake showed a poor CD4 recovery after initiation of HAART [13,17,18]. In adults and particularly when infected with HIV virus, the thymus is inactive due to involution of the thymus and the destruction of CD4 Tlymphocytes by the virus.…”
Section: Fdg Uptake In Lymphoid Tissue In Relation To the Stage And Imentioning
confidence: 99%